trans-Chloridotetrakis(4-methylpyridine-κN)(nitrosyl-κN)ruthenium(II) bis(hexafluoridophosphate) acetone 0.75-solvate - Hasan Shamran Mohammed; Sonia Mallet-Ladeira; Benoit Cormary; Marine Tassé; Isabelle Malfant (IUCrData, 2017)
The title compound, [RuCl(NO)(C6H7N)4](PF6)2·0.75(CH3)2CO, comprises four ligands of 4-picoline in equatorial position around the central atom. Overall, the complex features an octahedral coordination environment around the central RuII atom, with the chlorido ligand trans to the nitrosyl. The bond length of the nitrosyl N=O ligand is 1.140 (5) Å, while the angle Ru—N=O is 179.0 (4)°. The asymmetric unit contains four PF6− counter-anions, two with occupancy of 0.25 and one with occupancy of 0.5. One PF6− anion is disordered over two sets of sites and one other is disordered with an acetone molecule that occupies the same site.